The effects of metal cofactors on the reactivity of quercetin 2, 4-dioxygenase: synthetic model studies with M(ii)-complexes (M = Mn, Co, Ni, Cu, Zn) and assessment of the regulatory factors in catalytic efficacy. Issue 44 (31st October 2022) - Podder, Nirmalya; Mandal, Sukanta
Abstract : This paper demonstrates the metal ion effects on the dioxygenation of flavonol catalysed by M(ii )-complexes (M = Mn, Co, Ni, Cu, Zn) as functional models of quercetin 2, 4-dioxygenase-like reactivity. Abstract : This paper demonstrates the metal ion effects on the quercetin 2, 4-dioxygenase (2, 4-QD)-like reactivity. For this purpose, a series of five metal(ii )–acetato complexes [M II (L)(OAc)] M = Mn (1 OAc ), Co (2 OAc ), Ni (3 OAc ), Cu (4 OAc ), Zn (5 OAc ); OAc = acetate supported with a newly designed N3 O-donor carboxylato ligand L − L − = 2-((benzyl((6′-methyl-[2, 2′-bipyridin]-6-yl)methyl)amino)methyl)benzoate has been synthesised as models for the active sites of M II -substituted 2, 4-QDs. The enzyme–substrate (ES) model complexes [M II (L)(fla)] M = Mn (1 fla ), Co (2 fla ), Ni (3 fla ), Cu (4 fla ), Zn (5 fla ); flaH = flavonol have been synthesised by reacting flaH with their corresponding acetate-bound complexes in basic conditions. Detailed physicochemical properties of all the compounds are reported. Furthermore, single-crystal X-ray diffractions have been done to determine the structures of the compounds 2 OAc ·2H2 O, 3 OAc, 4 OAc ·CH2 Cl2 ·2H2 O, 5 OAc ·2H2 O and 2 fla ·MeOH . The enzymatic reactivities of complexes 1 OAc –5 OAc towards the dioxygenation of flavonol have been explored in detail. All the complexes effectively catalyse the oxygenative degradation of flavonol in N, N -dimethylformamide (DMF) medium at 70 °C under multiple-turnover conditions and produce enzyme-type products. Kinetic investigations were performed to see the metal ions' effects on reactivity. The reaction rates vary with the metal ions, showing the order Co > Ni > Zn > Mn > Cu. The studies reveal that the reactivities of the [M II (L)(OAc)] complexes are governed primarily by three factors viz the ES adduct formation constant ( K f ), the redox potential ( E pa ) of the bound fla − /fla˙ couple, and the degree of delocalisation of the fla˙ radical with the metal electrons, which are drastically influenced by the M 2+ ions. In the mechanistic interpretation, a single-electron transfer (SET) from the bound-flavonolate to dioxygen has been proposed to generate the catalytically important "M(ii )–fla˙" radical and superoxide ion, which react further to bring about the dioxygenation reaction. The identification of the metal(ii )-bound flavonoxy radical intermediate for the case of cobalt using EPR spectroscopy and the detection of superoxide ion by NBT 2+ test and EPR spin-trapping experiment (DMPO test) are remarkable in envisaging the reaction pathway.